Green eggs and ham - Seuss, Dr. (New York : Beginner Books, 1988)
When Sam-I-am persist in pestering a grumpy grouch to eat a plate of green eggs and ham, perseverance wins the day, teaching us all that we cannot know what we like until we have tried it!
Keywords: Children's stories; Stories in rhyme